Characteristic features of unruptured intracranial aneurysms: predictive risk factors for aneurysm rupture. Issue 5 (2nd September 2009) - You, S-H; Kong, D-S; Kim, J-S; Jeon, P; Kim, K H; Roh, H K; Kim, G-M; Lee, K-H; Hong, S-C
Abstract : Background and purpose: The purpose of this study was to identify the risk factors predisposing to aneurysm rupture and to provide a reliable estimation for likelihood of rupture in unruptured intracranial aneurysms. Methods: The authors performed a nested case-control study of 290 aneurysms (123 unruptured aneurysms and 167 ruptured aneurysms) occurring during a prospective cohort study in 1493 consecutive patients with newly diagnosed intracranial aneurysm and were treated in a single institute between January 1995 and December 2006. Controls were matched for age, treatment group, number of lesion, sex, region and study period in which the incidence of ruptured and unruptured intracranial aneurysm was equivalently balanced. The authors assessed the predictive risk factors associated with aneurysmal rupture based on the clinical and angiographic findings reported in the patients' medical records. Results: Between January 1997 and December 2002, 167 patients with ruptured intracranial aneurysms were assigned to group 1, and 123 patients with unruptured intracranial aneurysms during the same period were assigned to group 2. Aspect ratio (OR 3.76), maximum diameter of neck (Nmax ) ≤3 mm (OR 2.56) and family history of cerebrovascular disease (OR 5.63) were strongly correlated with aneurysm rupture (p<0.05). Conclusions: There are differences between the clinical and intrinsic characteristics of patients with unruptured and ruptured intracranial aneurysm. It will be helpful to make rational decisions regarding the optimal therapeutic strategy for unruptured intracranial aneurysm.